Role of Financial Literacy in Household Investment Decisions in Iraq - Baqir, George (American Journal of Finance, 2024)
Purpose: The aim of the study was to assess the role of financial literacy in household investment decisions in Iraq. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that households with higher levels of financial literacy tend to make more informed and effective investment choices, which lead to better financial outcomes. These households are more likely to participate in financial markets, diversify their investments, and utilize a broader range of financial instruments, which helps in mitigating risks and enhancing returns. Financially literate individuals are also more adept at understanding complex financial products, assessing investment risks, and planning for long-term financial goals such as retirement. Conversely, a lack of financial literacy can result in poor financial decisions, leading to lower participation in the stock market, inadequate savings, and suboptimal investment portfolios. Thus, enhancing financial literacy is essential for empowering households to make sound investment decisions, ultimately contributing to greater financial stability and wealth accumulation. Implications to Theory, Practice and Policy: Behavioral finance theory, portfolio theory and agency theory may be used to anchor future studies on assessing the role of financial literacy in household investment decisions in Iraq. In terms of practical recommendations, developing and implementing targeted financial education programs is essential. These programs should focus on improving specific aspects of financial literacy relevant to investment decisions. From a policy perspective, advocating for policies that support the integration of financial literacy education into school curricula at all levels is essential.